FULL DAY SCHOOL VS. MODULAR EDUCATION SYSTEM: A COMPARATIVE STUDY OF INDONESIA AND THE UNITED KINGDOM - Ika Kurnia Sofiani; Mardiana; Nurlidia Putri; Fitri Barokah (PT. Jurnal Center Indonesia Publisher, 2025)
The transformation of Indonesia's education system faces significant challenges in aligning with the demands of globalization, digitalization, and lifelong learning. These challenges have sparked debates regarding the effectiveness of the full-day school model and the modular education system. This study aims to comparatively analyze these two approaches within the context of primary and secondary education in Indonesia, referencing modular education practices in the United Kingdom as an international benchmark. The study employs a qualitative approach based on a literature review, utilizing thematic content analysis of 20 accredited scholarly sources selected through strict inclusion criteria, and analyzed with the assistance of NVivo software to ensure thematic accuracy.The findings indicate that the full-day school model excels in fostering discipline and consistent learning structures; however, it poses risks of cognitive fatigue and is less supportive of differentiated instruction. In contrast, the modular system offers flexibility, opportunities for personalized learning, and deeper conceptual understanding, yet requires adequate digital infrastructure and self-directed learning literacy, which are not evenly distributed.The study concludes that no single educational model is universally superior; instead, each holds contextual relevance. This research contributes theoretically by enriching the comparative education literature and practically by informing the design of more adaptive, inclusive, and responsive learning policies to meet the challenges of the 21st century, while also supporting efforts to achieve quality education as outlined in the Sustainable Development Goals (SDGs).